The Transformation of Education in The Era of Disruption: Challenges and Opportunities Towards The Future (Program Studi Magister Pendidikan Agama Islam Universitas Hasyim Asy’ari Tebuireng Jombang m Asy'ari, 2023)
This study explores the transformative impact of digital technology on education, emphasizing two important aspects: increased student engagement through interactive tools and the importance of achieving equitable access and digital inclusivity. Findings reveal that smart boards and educational apps contribute significantly to dynamic and personalized learning experiences, and revolutionize traditional pedagogy. However, challenges remain in ensuring equal access to digital resources, particularly evident in the digital divide. To bridge this gap, comprehensive policies, teacher empowerment and community involvement are needed to create an inclusive digital education ecosystem. These findings underscore the need to view technology not only as an educational tool but also as a means to bridge gaps and create a more equitable and inclusive educational future Studi ini mengeksplorasi dampak transformatif teknologi digital terhadap pendidikan, dengan menekankan dua aspek penting: peningkatan keterlibatan siswa melalui alat interaktif dan pentingnya mencapai akses yang adil dan inklusivitas digital. Temuan mengungkapkan bahwa papan pintar dan aplikasi pendidikan berkontribusi signifikan terhadap pengalaman belajar yang dinamis dan personal, serta merevolusi pedagogi tradisional. Namun, masih terdapat tantangan dalam memastikan akses yang setara terhadap sumber daya digital, terutama yang terlihat dalam kesenjangan digital. Untuk menjembatani kesenjangan ini diperlukan kebijakan yang komprehensif, pemberdayaan guru, dan keterlibatan masyarakat untuk menciptakan ekosistem pendidikan digital yang inklusif. Temuan ini menggarisbawahi perlunya memandang teknologi tidak hanya sebagai alat pendidikan namun juga sebagai sarana untuk menjembatani kesenjangan dan menciptakan masa depan pendidikan yang lebih adil dan inklusif.